Influence of pretreatment social support on health‐related quality of life in head and neck cancer survivors: Results from a prospective study12. Issue 6 (19th June 2012) - Howren, M. Bryant; Christensen, Alan J.; Hynds Karnell, Lucy; Van Liew, Julia R.; Funk, Gerry F.
Abstract Background Head and neck cancer and its treatment can have considerable impact on health‐related quality of life (HRQOL). The present study investigated whether social support, assessed before treatment, predicted HRQOL outcomes up to 12 months later in head and neck cancer survivors. Methods Using a prospective longitudinal design, patients (n = 364) were assessed on several clinical and psychosocial characteristics at diagnosis and then at 3‐ and 12‐month follow‐up appointments. HRQOL was assessed with the Short Form Health Survey (SF‐36) and the Head and Neck Cancer Inventory (HNCI). Results Hierarchical multiple regression analyses demonstrated that greater perceived support present at diagnosis significantly predicted more favorable global and head and neck cancer‐specific HRQOL at 3‐ and 12‐month follow‐up. Conclusion Results suggest that adequate social support at diagnosis can have a significant, positive impact on HRQOL in head and neck cancer survivors. Thus, it may be useful to evaluate support resources at diagnosis in order to identify individuals at risk for poor HRQOL outcomes. © 2012 Wiley Periodicals, Inc. Head Neck, 2012